A historical study of Mongols: The relevance of genghis khan’s leadership in the modern era - Kusumawardhani, Chandra; Simorangkir, Arnold Hiras; Widjayanto, Joni; Sutanto, S; Saputro, Guntur Eko (UNIVERITAS PGRI MADIUN, 2026)
Contemporary leadership is generally based on the context of modern organizations and does not conduct much research on historical leadership models that once shaped large-scale government systems. This study was conducted in an effort to fill this gap by analyzing the leadership of Genghis Khan, which has often been reduced to narratives of conquest and violence, without being analyzed as a structured leadership system. The study aims to analyze the principles of Genghis Khan's leadership and assess its relevance to modern leadership and management paradigms. This study uses a systematic literature review method by synthesizing 22 selected scientific sources consisting of classical historical texts and reputable journal articles with a thematic analysis approach. The results of the study identify five main themes, namely the historical context of Mongolia, leadership theory, meritocracy and organizational justice, servant leadership and social empathy, and value-based leadership. These findings show that Genghis Khan's leadership was a crucial factor in the success of the Mongol Empire, which was characterized by merit-based governance, adaptive organizational structures, strategic intelligence, and moral accountability. These leadership principles remain relevant and applicable in facing the complex and dynamic challenges of contemporary leadership and organizations.